Building sustainability in an Indigenous family owned SME in northern Australia: Overcoming operational barriers in a housing construction venture - Pearson, Cecil; Liu, Yi; Helms, K. (Society for Global Business & Economic Development (SGBED), 2011)
Identifying pathways for small to medium sized enterprises (SMEs), as potential entrants to the international market place, encourages evalutation how entrepreneurial activity can overcome encountered barriers to economic development. In an expression of commitment to improving the socio economic welfare of Indigenous people the Australian Government is encouraging Aboriginal involvement in entrepreneurial ventures, and integrating this notion in a local housing construction business has potential to improve the persistent poor living conditions in remote Australian Aboriginal communities. This paper describes an accomodation building programme initiated by the Yolngu people of East Arnhem Land of Australia, and with illustrations shows location and achivements. Revealing how the literature specified barriers to Australian Indigenous entrepreneurship were overcome provides a pathway worthy of consideration by rural Indigenous communities intending to engage in entrepreneurship, with vision to extent the life cycle of the firm into international markets.